Pengaruh Pandemi Covid-19 terhadap Tingkat Perceraian di Kota Bogor: - Muda Mamora; Sutisna Sutisna (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study examines the "Effect of the Covid-19 Pandemic on the Divorce Rate in Bogor City (Case Study in the Bogor Religious Court Class 1A". The purpose of this study was to determine the divorce rate in Bogor City during the COVID-19 pandemic and to find out how much influence the COVID-19 pandemic in Bogor City had on the divorce rate. In this study, a quantitative research approach was used, called quantitative because the research data was in the form of analytical figures using statistics, and the research method in this study used a simple linear regression method. The population that the authors took samples in this study were the people of Bogor City. The sampling technique in this study was determined by the author with a probability sampling technique, and the number of samples was 5%, which was as many as 100 people. Data collection techniques using questionnaires (questionnaires) as many as 30 items of statements, observations, documentation, and interview. Then the data that have been obtained, analyzed by the author using the correlation technique in SPSS 25. The results showed that there was a strong influence between the influence of the Covid-19 pandemic on the divorce rate in Bogor City, this was obtained from the rxy result of 0.639 which when viewed from the guideline table for the interpretation of the correlation value of the research variables, 0.639 lies in the coefficient 0.60 – 0.799, and the level of this coefficient is included in the level of strong influence. Keywords: society, covid-19 pandemic, divorce.